A vision of improvement of learning: South African teachers’ conceptions of classroom assessment - Jane, Sethusha Mantsose (Faculty of Education, University of the Free State, 2013)
This article explored conceptions that teachers hold about classroom assessment and how these conceptions influence their classroom assessment practices. The qualitative study employed a case study approach. Semi-structured interviews, observations and document analyses were used. The study utilized Brown’s (2004) conceptual framework on conceptions of assessment. The findings reveal that teachers’ conceptions of assessment are influenced by the social and education context in which they find themselves and that their personal experiences of assessment also influence their conceptions of assessment.
Keywords: Conceptions; Classroom assessment; Social context; Classroom practice; Assessment methods; Assessment techniques